Penerapan Konsep Peeragogy dalam Pembelajaran Tenses pada English Meeting Club Program Studi Tadris Bahasa Inggris - Harmilawati; Dewi Purnama, Atmaranie; Tamrin, Muhammad; Ulfayanti; Batari Muyassara, Andi; Ramadhan, Wahyu (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
Learning English especially tenses is still a scary thing to learn for most students. However, the English Education Study Program has a forum that provides space for students to actualize themselves in practicing to become peer tutors, namely the English Meeting Club. The purpose of this study is to find out the application of the concept of peeragogy in learning tenses at the English Meeting Club in the English Language Education Study Program. The method used in this study was descriptive qualitative with a sample of English Education study program students consisting of 3 (three) batches. Data collection techniques using observation, interviews and documentation with data analysis using the theory of Miles and Huberman. The results obtained from this study are related to the concept of applying peeragogy in learning tenses at the English Meeting Club of the English Education Study Program, namely the teacher (mentor) is a student of English Education Study Program who every week has been arranged in turns by presenting different tenses themes. Material presentation techniques were dominated by discussions and games. In addition, the teacher also provides tricks and tips that make it easier for students to better understand tenses material. The presentation of this material is also not only done in the classroom, but is carried out outside the classroom, both in the afternoon and at night.